Distigmatisation of Apprenticeship – A Vehicle for Entrepreneurship Promotion and Job Creation among Further Education and Training College Students - Odora, RJ; Naong, MN (SAGE Publications: Journal of Asian and African Studies, 2014)
The intention of this paper is two-fold; firstly, it is to explore the causal effect of perceived negativity towards Further Education and Training (FET) college education among South African youth. Secondly, it is to determine the impact of apprenticeship on the development of entrepreneurial knowledge and skills among FET college students. The FET sector serves a particular function, which is the imparting of hands-on vocational training, intended to inculcate and promote a culture of self-employment, considered a necessity for employment creation. A questionnaire was used to collect data from 112 randomly selected students from three Motheo FET colleges. The findings reveal very contrasting results, a direct correlation between apprenticeship and entrepreneurship; however, 53% of the respondents did not feel sufficiently equipped, ready and confident enough to start their own businesses after graduation. About 48% feel the need to further their studies at university in order to stand a better chance of landing a good job.
Published Article
Keywords: Distigmatisation; apprenticeship; Further Education; Training students; entrepreneurship; job creation; self-employment